Question of Identity: Mimicry and Decolonization in Jhumpa Lahiri’s Selected Short Stories - Abdullah, Omar Mohammed; Fayadh, Zainab Hummadi (Al-Adab Journal, 2020)
Since Jhumpa Lahiri has been regarded as a second generation Indian immigrant living in the United States. This has made her fully aware of the cultural mixing between India and America. This paper focuses on the process of mimicry and decolonization of Indian immigrants who live in the United States. Lahiri’s fiction Interpreter of Maladies reveals cultural identity, mimicry and decolonization that the immigrants experience while living in the target culture. This paper applies Homi Bhabha’s concept of mimicry and Frantz Fanon’s concept of decolonization to explore three short stories in Lahiri’s fiction Interpreter of Maladies namely; “When Mr. Pirzada Came to Dine” , “Mrs. Sen’s” and “This Blessed House”. The study concludes that some characters in these stories mimic the American culture as a result of their interaction with the Americans due to work or for being born and raised in America. Their imitation involves culture, tradition, language and religion. While, other characters decolonize and resist the American culture by rejecting everything related to this culture, in order to adhere to their original Indian identity and keep ties with their heritage.